Edukasi Terhadap Ibu Bayi Dalam Upaya Preventif Stunting Di Wilayah Kerja Puskesmas Moncongloe - Fitri, Lidia; Sakriawati, Sakriawati; Yusraa, Yusraa; Muslimin, Muslimin; Anurogo, Dito; Jamin, Nunung Suryana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Stunting is a major nutritional problem that will have an impact on social and economic life in society. There is clear evidence that stunted individuals have higher rates of death from various causes and increased incidence of disease. Stunting will affect physical work performance, mental and intellectual functions will be disrupted and is associated with impaired immune function and increases the risk of death. Stunting is a nutritional problem that arises due to a lack of nutritional intake, resulting in impaired growth in children. This community service activity is carried out with the aim of increasing mothers' knowledge about stunting and its prevention efforts. The educational method used is through counseling. Activities are carried out in pre-test stages, providing education through counseling about stunting and its prevention, and finally a post-test. Data analysis was carried out using the Paired Samples T-Test with the subjects namely mothers with toddlers aged 6-24 months. The results show that there is an increase in the average knowledge score of mothers after receiving education, namely 11.19 points, the average pre-test score = 70.27 and the average post-test score = 81.46. The results of statistical analysis show a significance value of 0.000 (< 0.05), so it can be concluded that providing education through counseling has an effect on increasing mothers' knowledge regarding stunting and its prevention efforts.